2‐deoxyglucose and β‐hydroxybutyrate fail to attenuate seizures in the betamethasone‐NMDA model of infantile spasms. Issue 1 (24th November 2021) - Janicot, Remi; Shao, Li‐Rong; Stafstrom, Carl E.
Abstract: Infantile spasms (IS) is an epileptic encephalopathy with a poor neurodevelopmental prognosis, and limited, often ineffective treatment options. The effectiveness of metabolic approaches to seizure control is being increasingly shown in a wide variety of epilepsies. This study investigates the efficacy of the glycolysis inhibitor 2‐deoxyglucose (2‐DG) and the ketone body β‐hydroxybutyrate (BHB) in the betamethasone‐NMDA model of rat IS. Prenatal rats were exposed to betamethasone on gestational day 15 (G15) and NMDA on postnatal day 15 (P15). Video‐electroencephalography (v‐EEG) was used to monitor spasms. NMDA consistently induced hyperflexion spasms associated with interictal sharp‐slow wave EEG activity and ictal flattening of EEG signals, reminiscent of hypsarrhythmia and electrodecrement, respectively. 2‐DG (500 mg/kg, i.p), BHB (200 mg/kg, i.p.), or both were administered immediately after occurrence of the first spasm. No experimental treatment altered significantly the number, severity, or progression of spasms compared with saline treatment. These data suggest that metabolic inhibition of glycolysis or ketogenesis does not reduce infantile spasms in the NMDA model. The study further validates the betamethasone‐NMDA model in terms of its behavioral and electrographic resemblance to human IS and supports its use for preclinical drug screening.